Croton carajasensis, a new species from Serra dos Carajás, Pará, Brazilian Amazon - Sodré, Rodolfo Carneiro; Secco, Ricardo De S. (Phytotaxa, 2023)
During a floristic survey of Euphorbiaceae in cangas (areas of iron-rich soils) of the Serra dos Carajás (Pará State, Brazil), a new species of Euphorbiaceae was found. Croton carajasensis is only known from cangas vegetation and it is herein described and illustrated. The relationships of the new taxon with the most morphologically similar species (C. abaitensis, C. adamantinus, C. harleyi and C. ramosissimus) and its infrageneric position are discussed. We also include a distribution map, comments on habitat, flowering, fruiting, and a preliminary assessment of the species’ conservation status.